A textbook of human physiology - Gurumurthy, H.; Makari, H. K.; Patil, H. S. Ravikumar; Sowmya, S. V. (I.K. International Publishing House, 2010)
Human physiology is the science of the mechanical, physical, and biochemical functions of humans. Physiology is the most fascinating and ancient branch of science. It unfolds the mystery of complicated functions of the body system and individual organs in the body. This book provides the various aspects of Human Physiology.